Hero - Lupica, Mike. (New York : Philomel Books, 2010)
Fourteen-year-old Zach learns he has the same special abilities as his father, who was the president's globe-trotting troubleshooter until "the Bads" killed him, and now Zach must decide whether to use his powers in the same way at the risk of his own life.
School Library Journal, December 2010
Publisher's Weekly, October 2010
Booklist, October 2010
4.6
5-8
Keywords: Heroes -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Politics, Practical -- Juvenile fiction; Death -- Juvenile fiction; Families -- New York (State) -- New York -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Heroes -- Fiction; Fathers and sons -- Fiction; Politics, Practical -- Fiction; Death -- Fiction; Family life -- Fiction; New York (N.Y.) -- Fiction; Heroes and heroines -- Fiction; Father-son relationship -- Fiction; Politics -- Fiction; Death -- Fiction; Family life -- New York (N.Y.) -- Fiction